Pengaruh Brand Ambassador, Daya Tarik Iklan, dan Product Packaging Terhadap Keputusan Pembelian Produk Kosmetik Wardah Exclusive Matte Lip Cream: Studi pada Masyarakat di Kabupaten Kebumen - Gracelda Asprila Sasongko; Harini Abrilia Setyawati (LP3M Universitas Putra Bangsa, 2022)
The purpose of this study was to determine the effect of Brand Ambassador, Advertising Attractiveness and Product Packaging on Purchase Decisionns on Wardah Exclusive Matte Lip Cream cosmetic products (Study on Communities in Kebumen Regency). Data was collected using a questionnaire, using a Likert scale 4. This study took 100 respondents. The method used is purposive sampling. The data analysis technique in this research uses Validity Test, Reliability Test, Classical Assumption Test (Multicollinearity Test, Heteroscedasticity Test and Normality Test), Multiple Linear Regression Test, and Hypothesis Testing (Partial Test / t Test, Simultaneous Test / F Test, and Coefficients determination). Data processing in this study used SPSS (Statistical Package For the Social Sciences) software version 20.0. The results of this study indicate that it is known that the brand ambassador has no effect on the purchase decision of Wardah exclusive matte lip cream cosmetic products. The attractiveness of advertisements does not affect the Purchase Decision of Wardah Cosmetics Exclusive Matte Lip Cream. Product packaging has a significant effect on the purchasing decision of Wardah exclusive matte lip cream. Brand ambassador, advertising attractiveness, and product packaging have a significant simultaneous (together) effect on the Purchase Decision of Wardah Exclusive Matte Lip Cream Cosmetic Products in the community in Kebumen Regency.